Behavior of Trip Length Distribution Pattern due to the Variation of Trip Length Interval Determination - Hitapriya Suprayitno; Vita Ratnasari; Nina Saraswati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Transport Model is always needed and important for developing Transportation System Master Plan. Trip Distribution is one of the important parts of Transport Model, which is a result mathematical operation of trip generation and deterrence function. Trip Length Distribution Pattern is the foundation of Deterrence Function. The trip length distribution pattern can change due to the various trip length interval used. Analog to this, the Deterrence Function can also change. The research result indicate that the distribution pattern change significantly on trip length interval 1 to 3 km. For trip length interval of 4 to 8 km, the trip length distribution indicate the general characteristic of trip length distribution, i.e. the number of trips is high in short distance and getting down in the longer trip distance. The trip interval of 7 km gives the most accepted Tanner Deterrence Function.